Design and Formulation of Hydrogel Sponges for Mesenchymal Stem Cell Secretome Delivery - Noviza, Deni; Ardelia, Syahda Permata; Marlina (Science and Technology Indonesia, 2026)
The mesenchymal stem cells (MSCs) secretome plays multiple roles in tissue regeneration and wound healing due to its content of various bioactive factors, including Fibroblast Growth Factor-2 (FGF-2). To support its topical application, an effective delivery system is required to preserve the stability and bioactivity of the secretome. A hydrogel sponge based on PVA-HPMC-PEG was selected as the delivery matrix due to its porous structure, flexibility, and ability to release active substances, thereby making it a promising candidate for wound healing applications. The objective of this research was to formulate a PVA-HPMC-PEG-based hydrogel sponge for a secretome delivery system. The hydrogel sponge was prepared using the freeze-drying method and optimized by varying the PVA concentration to achieve the desired physicochemical characteristics. The optimal formulation (F4) consists of 20% PVA, 2% HPMC, and 7.5% PEG. Evaluation revealed that this formulation exhibited a flexible sponge-like structure with a swelling percentage of 279.793% ± 0.06, elongation percentage of 107.923% ± 4.98, and physical crosslinking confirmed by FTIR analysis. Scanning Electron Microscopy (SEM) analysis demonstrated pore size ranging from 20 to 215 μm. Furthermore, secretome release was assessed using a Franz diffusion cell, and FGF-2 levels were quantified via ELISA. The results confirmed that the hydrogel sponge effectively facilitated the release of the secretome.